Simplified risk-prediction for benchmarking and quality improvement in emergency general surgery. Prospective, multicenter, observational cohort study. (January 2022) - Villodre, C.; Taccogna, L.; Zapater, P.; Cantó, M.; Mena, L.; Ramia, J.M.; Lluís, F.; Afonso, N.; Aguilella, V.; Aguiló, J.; Alados, J.C.; et al.
Abstract: Background and aims: Emergency General Surgery (EGS) conditions account for millions of deaths worldwide, yet it is practiced without benchmarking-based quality improvement programs. The aim of this observational, prospective, multicenter, nationwide study was to determine the best benchmark cutoff points in EGS, as a reference to guide improvement measures. Methods: Over a 6-month period, 38 centers (5% of all public hospitals) attending EGS patients on a 24-h, 7-days a week basis, enrolled consecutive patients requiring an emergent/urgent surgical procedure. Patients were stratified into cohorts of low (i.e., expected morbidity risk <33%), middle and high risk using the novel m-LUCENTUM calculator. Results: A total of 7258 patients were included; age (mean ± SD) was 51.1 ± 21.5 years, 43.2% were female. Benchmark cutoffs in the low-risk cohort (5639 patients, 77.7% of total) were: use of laparoscopy ≥40.9%, length of hospital stays ≤3 days, any complication within 30 days ≤ 17.7%, and 30-day mortality ≤1.1%. The variables with the greatest impact were septicemia on length of hospital stay (21 days; adjusted beta coefficient 16.8; 95% CI: 15.3 to 18.3; P < .001), and respiratory failure on mortality (risk-adjusted population attributable fraction 44.6%, 95% CI 29.6 to 59.6, P < .001). Use of laparoscopy (odds ratio 0.764, 95% CI 0.678 to 0.861; P < .001), and intraoperative blood loss (101–500 mL: odds ratio 2.699, 95% CI 2.152 to 3.380; P < .001; and 500–1000 mL: odds ratio 2.875, 95% CI 1.403 to 5.858; P = .013) were associated with increased morbidity. Conclusions: This study offers, for the first time, clinically-based benchmark values in EGS and identifies measures for improvement. Highlights: The best benchmark cut-offs in Emergency General Surgery are unknown. The present study established benchmark cut-off values in a low-risk cohort. Benchmark cut-off was ≥40.9% for use of laparoscopy, and ≤3 days for hospital stays. Benchmark cut-off was ≤17.7% for 30-day morbidity, and ≤1.1% for 30-day mortality. These cut-offs values may guide quality improvement in Emergency General Surgery.